Heat insulation and heat preservation multiphase ceramic fiber aerogel used in 1800 DEG C superhigh temperature environment and preparation method of heat insulation and heat preservation multiphase ceramic fiber aerogel

Alumina-zirconia-mullite fiber ceramic aerogel was prepared through multiphase competition strategy and sol-gel method, which solved the problem of structural instability of ceramic fiber aerogel in ultra-high temperature environment, and achieved the condition at 1800℃ The structural integrity and high-efficiency thermal insulation performance for long-term use of 1600°C.

CN119504271APending Publication Date: 2025-02-25SUZHOU ELMER TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411398794.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing ceramic fiber aerogels are difficult to maintain structural integrity in ultra-high temperature environments, resulting in limited application at temperatures above 1600°C.

Method used

Alumina-zirconia-mullite fiber ceramic aerogel was prepared by using a multiphase competition strategy, polyhydroxyzirconia was synthesized in one step by alkaline zirconium carbonate and glacial acetic acid, and aluminum silicone sol was prepared by sol-gel method at low temperature, and finally Electrospinning or centrifugal spinning technology to prepare fiber aerogels.

Benefits of technology

After 1800℃, the structure is kept intact after 100s. The aerogel line shrinkage rate does not exceed 3% at a long time of 1600℃. It has good performance and good flexibility. It does not require complex heat treatment or atmosphere protection, and is easy to industrial macro production. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504271A_ABST
    Figure CN119504271A_ABST
Patent Text Reader

Abstract

The invention discloses a thermal insulation multiphase ceramic fiber aerogel used in an ultrahigh temperature environment of 1800 DEG C and a preparation method of the thermal insulation multiphase ceramic fiber aerogel. The preparation method comprises the following steps: mixing basic zirconium carbonate, glacial acetic acid and a yttrium source according to a specific molar ratio to prepare a zirconium precursor solution; the preparation method comprises the following steps: adding an aluminum source and a silicon source into a solvent according to a specific molar ratio, completely dissolving to obtain a silicon-aluminum solution, condensing and refluxing until the solution is completely clarified to prepare a silicon-aluminum precursor solution, mixing the silicon-aluminum precursor solution with the silicon-aluminum precursor solution according to a specific molar ratio, solating to obtain a zirconium-silicon-aluminum ternary sol, adding a spinning aid into the zirconium-silicon-aluminum ternary sol to obtain a zirconium-aluminum-silicon ternary spinning solution, and carrying out spinning on the zirconium-silicon-aluminum ternary spinning solution to obtain the zirconium-silicon-aluminum ternary spinning solution. And carrying out electrostatic spinning or centrifugal spinning on the zirconium-aluminum-silicon ternary spinning solution to obtain a zirconium-aluminum-silicon fiber aerogel precursor, collecting the zirconium-aluminum-silicon fiber aerogel precursor, heating to 1000-1300 DEG C, carrying out heat preservation, and cooling along with a furnace to obtain the aluminum oxide-zirconium oxide-mullite fiber ceramic aerogel with a three-dimensional structure. The aerogel prepared by the method is good in flexibility and has a good three-dimensional pore structure, and the fiber surface is smooth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of submicron new materials, and in particular relates to a heat insulating and heat preserving multiphase ceramic fiber aerogel for use in an ultra-high temperature environment of 1800°C and a preparation method thereof. Background Art

[0002] At present, the most widely used thermal insulation ceramic aerogel is the traditional silica aerogel composed of zero-dimensional hollow nanoparticles. Although the mechanical properties are enhanced by using fibers, their brittle nature and low elastic strain capacity still limit their application. Domestic and foreign researchers mainly overcome the brittleness of ceramics and improve their thermal stability by manufacturing flexible one-dimensional fiber structures, and have developed pure one-dimensional fiber ceramic aerogels, such as SiO2 nanofiber ceramic aerogels and ZrO2 nanofiber ceramic aerogels.

[0003] Silicon-based nanofiber ceramic aerogel is considered to be a promising thermal insulation material. Ding Bin et al. prepared SiO2 nanofiber ceramic aerogel by electrospinning combined with secondary cross-linking directional freezing, and obtained good mechanical properties. Experiments show that the prepared aerogel has excellent thermal insulation properties under high temperature conditions of 1100°C. However, due to the inherent high-temperature collapse and softening properties of SiO2 materials, its application in ultra-high temperature fields is limited.

[0004] Zirconium-based nanofiber ceramic aerogels have attracted much attention in the ultra-high temperature field, which is not only due to the high melting point of ZrO2, but also due to the fact that ZrO2 has a certain ability to reflect heat transfer mainly by thermal radiation in high temperature areas.

[0005] Mullite (3Al2O3·2SiO2) fiber ceramic aerogel is a newly prepared product in recent years that can be used at very high temperatures and has very good anti-oxidation properties, which greatly improves its service life. In the exploration and research of it for many years, further increasing the aluminum content can obtain alumina-mullite composite ceramics, which are characterized by high refractoriness and good chemical and thermal stability. It has the advantages of high temperature resistance, high strength, and wear resistance of alumina ceramics, and the advantages of low thermal expansion coefficient, creep resistance, and thermal shock resistance of mullite.

[0006] The long-term service temperature of existing ceramic fiber aerogels is difficult to reach above 1600°C. The main problem can be attributed to the collapse and pulverization of the fiber structure caused by the rapid growth of aerogel grains, which ultimately leads to the loss of performance.

[0007] In order to expand the application prospects of ceramic aerogel materials in ultra-high temperature environments, there is an urgent need to use a multiphase competition strategy to prepare fiber ceramic aerogels with high reflected thermal radiation, good mechanical properties, slow grain growth rate, and excellent high-temperature structural stability. Summary of the invention

[0008] The working temperature of traditional ceramic fiber aerogels is difficult to reach above 1600°C, which leads to the problem of limiting their application in the ultra-high temperature field. The purpose of the present invention is to provide a thermal insulation and heat preservation multiphase ceramic fiber aerogel for use in an ultra-high temperature environment of 1800°C and a preparation method thereof, which can meet the requirements of mechanical and thermal integration enhancement in an ultra-high temperature environment.

[0009] The technical solution adopted by the present invention is as follows: a method for preparing a heat-insulating multiphase ceramic fiber aerogel for use in an ultra-high temperature environment of 1800°C, the steps are as follows:

[0010] Step 1: Under a temperature condition of 40-60° C., mixing and stirring at a molar ratio of basic zirconium carbonate: glacial acetic acid: yttrium source = 1: (1-2.5): 0.02 to prepare a zirconium precursor solution; wherein the yttrium source is yttrium acetate, yttrium nitrate, yttrium chloride or any mixture thereof;

[0011] Step 2: at a temperature of 40 to 60° C., mixing an aluminum source and a silicon source in a molar ratio of (3 to 5):1, adding the mixture to a solvent and stirring until completely dissolved to obtain a silicon-aluminum solution, condensing and refluxing the silicon-aluminum solution at a temperature of 80 to 90° C. until the solution is completely clarified, thereby obtaining a silicon-aluminum precursor solution; wherein the aluminum source is aluminum isopropoxide, aluminum nitrate, aluminum chloride, aluminum acetylacetonate or any mixture thereof; and the silicon source is tetraethyl silicate, 3-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane or a mixture thereof;

[0012] Step 3: at a temperature of 40-60° C., the zirconium precursor solution and the silicon-aluminum precursor solution are mixed uniformly in a molar ratio of zirconium source: silicon source = (1-3):1, and stirred sufficiently to form a sol, thereby finally obtaining a zirconium-silicon-aluminum ternary sol;

[0013] Step 4: adding a spinning aid to the zirconium-silicon-aluminum ternary sol, stirring at a temperature of 25 to 60° C. until the spinning aid is completely dissolved, the stirring time is 1 to 6 hours, and adjusting the solution viscosity to 1 to 10 Pa·s, and finally obtaining a zirconium-aluminum-silicon ternary spinning solution;

[0014] Step 5: Control the temperature to 24-26° C. and the humidity to 50%, electrospin or centrifuge the zirconium-aluminum-silicon ternary spinning solution, the spinning aperture is 0.05-0.3 mm, and obtain the zirconium-aluminum-silicon fiber aerogel precursor and collect it;

[0015] Step six: Heat the collected zirconium aluminum silicate fiber aerogel precursor to 1000-1300°C at a heating rate of 0.5-2°C / min in an air atmosphere, keep it warm for 0.5-2h, and then cool it down with the furnace to finally obtain alumina-zirconia-mullite fiber ceramic aerogel with a three-dimensional structure.

[0016] Furthermore, in step 1, basic zirconium carbonate, glacial acetic acid and yttrium source are mixed and stirred for 1 to 12 hours.

[0017] Furthermore, the aluminum source and the silicon source are mixed and added into the solvent and stirred for 1 to 12 hours until they are completely dissolved.

[0018] Furthermore, the solvent in step 2 is deionized water, methanol, ethanol, isopropanol or any mixture thereof.

[0019] Furthermore, the spinning aid in step 4 is polyethylene oxide PEO, polyvinyl pyrrolidone PVP, polyvinyl alcohol PVA or any mixture thereof.

[0020] Furthermore, the mass ratio of the spinning aid described in step 4 to the zirconium-silicon-aluminum ternary sol is (0.001-0.1):1, and the viscosity is adjusted to 1-10 Pa·s.

[0021] Another object of the present invention is to provide a thermal insulation and heat preservation multiphase ceramic fiber aerogel for use in an ultra-high temperature environment of 1800°C, which is prepared according to the preparation method as described above.

[0022] Furthermore, the aerogel as described above maintains structural integrity after being subjected to a temperature of 1800° C. for 100 seconds, and the linear shrinkage of the aerogel does not exceed 3% at a long-term temperature of 1600° C.

[0023] The advantages and beneficial effects of the present invention are as follows: the present invention synthesizes polyhydroxy zirconium in one step with basic zirconium carbonate and glacial acetic acid, does not contain other impurity anions, and the increased organic content is conducive to spinning and is environmentally friendly. The present invention adopts the sol-gel method to prepare aluminum silicate sol at low temperature, effectively avoiding the high energy consumption and high production process equipment requirements caused by the high-temperature melting preparation of traditional mullite fibers, and has low cost. The alumina-zirconia-mullite fiber ceramic aerogel prepared by the present invention has good performance and flexibility, the disordered winding of the fibers has a good three-dimensional pore structure, and the fiber surface is smooth. The structure remains intact after 100s under 1800°C, and the linear shrinkage rate of the aerogel does not exceed 3% at a long-term temperature of 1600°C. The present invention does not require complex heat treatment, does not require atmosphere protection, and is easy to industrialize and mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1The SEM photos and element mapping distribution diagrams of the alumina-zirconia-mullite fiber ceramic aerogel fibers obtained in Example 1. (a) is a three-dimensional overlap diagram between the aerogel fibers, (b) is the single fiber morphology after aerogel molding, (c) is the single fiber morphology after aerogel long-term heat treatment at 1600°C, (d) is the single fiber morphology after aerogel short-term heat treatment at 1800°C, and (e) is the energy spectrum mapping distribution diagram of each element of aerogel single fiber.

[0025] Figure 2 These are the XRD spectra of the alumina-zirconia-mullite fiber ceramic aerogel fibers obtained in Example 1 after heat treatment at 1300°C, at 1600°C for 24 hours, and at 1800°C for 100 seconds. DETAILED DESCRIPTION

[0026] The present invention is further described below with reference to examples and drawings, but is not limited thereto. The chemical reagents and equipment used in each example are conventional commercial products.

[0027] Embodiment 1:

[0028] A multiphase ceramic fiber aerogel for heat insulation in an ultra-high temperature environment of 1800°C and a preparation method thereof, comprising the following steps:

[0029] S1: Weigh 100 g of basic zirconium carbonate, 50 g of glacial acetic acid, and 3.98 g of yttrium nitrate hexahydrate into a beaker, and stir in a water bath at 60° C. until the solution is completely clear to form a polyhydroxy zirconium oxide precursor solution.

[0030] S2: Weigh 61.52 g of aluminum nitrate, 61.28 g of aluminum isopropoxide and 24.3 g of tetraethyl orthosilicate and dissolve them in a beaker containing an appropriate amount of deionized water. Stir at room temperature for 12 h until the solution becomes a light gray clear solution. Pour the mixture into a three-necked flask and condense and reflux in an oil bath at 85°C until the solution is completely clear and transparent, thereby obtaining a silicon-aluminum precursor solution.

[0031] S3: Stir the zirconium precursor solution prepared in step S1 and the silicon-aluminum precursor solution prepared in step S2 at 60° C. for 6 hours to finally prepare a zirconium-silicon-aluminum ternary sol.

[0032] S4: Add 49.7 g of polyvinyl pyrrolidone (PVP) to the zirconium-silicon-aluminum ternary sol obtained in step S3, stir at 60°C until it is completely dissolved, continue to add deionized water to adjust the solution viscosity to 1 Pa·s, and finally obtain a spinnable zirconium-aluminum-silicon ternary spinning solution.

[0033] S5: Push the zirconium-aluminum-silicon ternary spinning solution into the syringe at a rate of 2 ml / h, control the temperature at 24°C ~ 26°C, the humidity condition at 50%, select a 23G electrospinning needle, the distance between the electrospinning needle and the conveyor belt collector connected to the negative electrode is 0.5m, control the electrospinning voltage to be stable at 25kV, and obtain the zirconium-aluminum-silicon fiber aerogel precursor.

[0034] S6: The obtained zirconium aluminum silicate fiber aerogel precursor is heated to 500°C at a heating rate of 1°C / min, and then heated to 1300°C at a heating rate of 2°C / min, kept at this temperature for 30 minutes, and cooled with the furnace to obtain alumina-zirconia-mullite fiber ceramic aerogel.

[0035] As attached Figure 1 As shown, the fibers of the alumina-zirconia-mullite fiber ceramic aerogel prepared in this embodiment are tightly overlapped and wound, and the fiber diameter is 1-10 μm. Figure 2 The XRD characterization analysis shown above shows that the aerogel has an alumina-zirconia-mullite multiphase crystal structure, has excellent mechanical and thermal properties, and can be used at a maximum temperature of 1800°C and a long-term temperature of 1600°C.

[0036] Embodiment 2:

[0037] The steps and parameters of the preparation method of this embodiment are roughly the same as those of Example 1, except that: in step S4, the viscosity of the zirconium-aluminum-silicon ternary spinning solution is adjusted to 8 Pa·s with deionized water, and then spinning is carried out using a centrifugal spinning machine. The spinning parameters are a rotation speed of 10000 rpm, a spinning aperture of 0.1 mm, and the environmental parameters are the same as those of Example 1.

[0038] Comparative Example 1:

[0039] The steps and parameters of the preparation method of this embodiment are roughly the same as those of embodiment 1, except that: in step S6, the heat treatment rate is increased to 1300°C at 5°C / min, kept at this temperature for 30 minutes, and cooled with the furnace, and alumina-zirconia-mullite fiber ceramic aerogel can also be obtained. The fiber is slightly pulverized, has poor flexibility, and becomes brittle.

[0040] Comparative Example 2:

[0041] The steps and parameters of the preparation method of this embodiment are roughly the same as those of embodiment 2, except that the spinning aperture in step S4 is changed to 0.5 mm for centrifugal spinning. The fiber diameter of the alumina-zirconia-mullite fiber ceramic aerogel obtained is relatively coarse, a large number of slag balls appear, the fibers are adhered, and pulverized after drying, and the fiber flexibility is poor.

[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several improvements and modifications can be made without departing from the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a heat-insulating multiphase ceramic fiber aerogel for use in an ultra-high temperature environment of 1800°C, characterized in that: The steps are as follows: Step 1: Under a temperature condition of 40-60° C., mixing and stirring at a molar ratio of basic zirconium carbonate: glacial acetic acid: yttrium source = 1: (1-2.5): 0.02 to prepare a zirconium precursor solution; wherein the yttrium source is yttrium acetate, yttrium nitrate, yttrium chloride or any mixture thereof; Step 2: at a temperature of 40 to 60° C., mixing an aluminum source and a silicon source in a molar ratio of (3 to 5):1, adding the mixture to a solvent and stirring until completely dissolved to obtain a silicon-aluminum solution, condensing and refluxing the silicon-aluminum solution at a temperature of 80 to 90° C. until the solution is completely clarified, thereby obtaining a silicon-aluminum precursor solution; wherein the aluminum source is aluminum isopropoxide, aluminum nitrate, aluminum chloride, aluminum acetylacetonate or any mixture thereof; and the silicon source is tetraethyl silicate, 3-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane or a mixture thereof; Step 3: at a temperature of 40-60° C., the zirconium precursor solution and the silicon-aluminum precursor solution are mixed uniformly in a molar ratio of zirconium source: silicon source = (1-3):1, and stirred sufficiently to form a sol, thereby finally obtaining a zirconium-silicon-aluminum ternary sol; Step 4: adding a spinning aid to the zirconium-silicon-aluminum ternary sol, stirring at a temperature of 25 to 60° C. until the spinning aid is completely dissolved, the stirring time is 1 to 6 hours, and adjusting the solution viscosity to 1 to 10 Pa·s, and finally obtaining a zirconium-aluminum-silicon ternary spinning solution; Step 5: Control the temperature to 24-26° C. and the humidity to 50%, electrospin or centrifuge the zirconium-aluminum-silicon ternary spinning solution, the spinning aperture is 0.05-0.3 mm, and obtain the zirconium-aluminum-silicon fiber aerogel precursor and collect it; Step six: Heat the collected zirconium aluminum silicate fiber aerogel precursor to 1000-1300°C at a heating rate of 0.5-2°C / min in an air atmosphere, keep it warm for 0.5-2h, and then cool it down with the furnace to finally obtain alumina-zirconia-mullite fiber ceramic aerogel with a three-dimensional structure.

2. The preparation method according to claim 1, characterized in that: In step 1, basic zirconium carbonate, glacial acetic acid and yttrium source are mixed and stirred for 1 to 12 hours.

3. The preparation method according to claim 1, characterized in that: In step 2, the aluminum source and the silicon source are mixed and added into the solvent and stirred for 1 to 12 hours until they are completely dissolved.

4. The preparation method according to claim 1, characterized in that: The solvent in step 2 is deionized water, methanol, ethanol, isopropanol or any mixture thereof.

5. The preparation method according to claim 1, characterized in that: In step 4, the spinning aid is polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA) or any mixture thereof.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the spinning aid described in step 4 to the zirconium-silicon-aluminum ternary sol is (0.001-0.1):1, and the viscosity is adjusted to 1-10 Pa·s.

7. A thermal insulation and heat preservation multiphase ceramic fiber aerogel for use in an ultra-high temperature environment of 1800°C, obtained by the preparation method according to any one of claims 1 to 6.

8. The heat insulating and heat preserving multiphase ceramic fiber aerogel for use in an ultra-high temperature environment of 1800°C according to claim 7, characterized in that: The aerogel maintains structural integrity after being subjected to a temperature of 1800° C. for 100 seconds, and the linear shrinkage rate of the aerogel does not exceed 3% at a long-term temperature of 1600° C.

Citation Information

Patent Citations

  • Preparation method for alumina-zirconia ceramic fiber

    CN103408292A

  • Method for preparing three-dimensional nanofiber ceramic aerogel through vortex field assisted electrostatic spinning

    CN113149655A

  • Precursor composite sol for aluminum oxide / mullite biphase fiber and preparation method of precursor composite sol

    CN114162844A

  • Preparation method of uniform and compact high-temperature continuous zirconium oxide filament

    CN115233336A

  • Preparation method of silicon oxide ceramic fiber aerogel heat insulation film

    CN117188046A

Cited By

  • High-temperature gradient composite aerogel material for directional solidification single crystal furnace and preparation method of high-temperature gradient composite aerogel material

    CN120794664A